2022
DOI: 10.21037/tcr-21-2611
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a three-miRNA panel in serum for bladder cancer diagnosis by a diagnostic test

Abstract: Background Bladder cancer (BC) is the tenth most common cancer in the world. Serum microRNA (miRNA) profiles previously have been reported as non-invasive biomarkers in cancer screening. The non-invasive and reliable diagnostic biomarkers are urgently needed for detecting BC, while cystoscopy is invasive. Our study aimed to identify candidate miRNAs in serum as potential diagnostic biomarkers for BC detection. Methods This study was including the screening stage, traini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
6
0
1
Order By: Relevance
“…Coupled with observations that BNC2 expression is lower in ovarian cancer cell lines compared with normal tissue (14) and that the deletion of SNP-containing regions decreases expression (11), BNC2 was thereby implicated as an important cancer-associated gene. Similar studies also note the association of BNC2-related SNPs across a range of cancer types (esophageal (15), prostate (16), bladder (17,18,19), liver (20), skin (21,22,23), uterus (24,25), stomach (26), and lung (27)).…”
Section: Introductionmentioning
confidence: 55%
“…Coupled with observations that BNC2 expression is lower in ovarian cancer cell lines compared with normal tissue (14) and that the deletion of SNP-containing regions decreases expression (11), BNC2 was thereby implicated as an important cancer-associated gene. Similar studies also note the association of BNC2-related SNPs across a range of cancer types (esophageal (15), prostate (16), bladder (17,18,19), liver (20), skin (21,22,23), uterus (24,25), stomach (26), and lung (27)).…”
Section: Introductionmentioning
confidence: 55%
“…At this time, as an initial precaution, we quantified the samples using the Spectrophotometer (Thermo Scientific™ NanoDrop™) to evaluate the purification of the extracted RNA. Regarding endogenous control and duplicate reactions, we did not find standardization in the literature, including studies published in recent years using a single endogenous miRNA for control ( Sekovanić et al, 2021 ; Bayati et al, 2022 ; Couto et al, 2022 ; Li et al, 2022 ; Ding et al, 2023 ; Higashi et al, 2023 ). Furthermore, Couto et al (2022) cite duplicate reactions and the other authors do not cite the number of reactions carried out.…”
Section: Discussionmentioning
confidence: 99%
“…Higher expression of miR-152 as well as lower expression of both miR-3187-3p and miR-27a-3p are associated with characteristics of a poorer prognosis of BC patients with characteristics of advanced clinical stage, higher tumor grade, and positive lymph node metastasis. Specifically, NMIBC patients with high miR-152 expression and low miR-3187-3p expression had a poor relapse-free survival, miR-152 was independently associated with tumor recurrence in NMIBC [41] , and miR-20a-5p was also associated with BC recurrence [40] . In addition, the expression levels of miR-210 were associated with the staging and grading of BC, and the expression of serum miR-210 was significantly decreased in postoperative paired specimens, but increased in most patients with recurrent BC [45] (Table 1).…”
Section: Mirna In Bloodmentioning
confidence: 97%
“…In contrast to microarray screening, however, high-throughput sequencing eliminates some potential contamination of other small RNA and DNA fragments. For example, Jiang et al [41] employed MiSeq to identify 26 differentially expressed miRNAs in BC, and found that the AUC for the combination of six miRNAs used for early BC diagnosis in patients with Ta and T1 stages was significantly higher (0.841), compared with that of urine cytology (0.645) [41] . In a study conducted by Li et al, a combination of four miRNAs was identified for BC diagnosis in the serum, demonstrating an exceptional diagnostic power with an AUC of 0.985 [42] .…”
Section: Mirna In Bloodmentioning
confidence: 99%